Randomized controlled trials of antiepileptic drugs for the treatment of post-stroke seizures: A systematic review with network meta-analysis. (October 2018) - Brigo, F.; Lattanzi, S.; Zelano, J.; Bragazzi, N.L.; Belcastro, V.; Nardone, R.; Trinka, E.
Highlights: Direct and indirect comparison of antiepileptic drugs for poststroke seizures. No difference between levetiracetam and lamotrigine for seizure freedom. More adverse events for levetiracetam than for lamotrigine. Levetiracetam and lamotrigine better tolerated than controlled-release carbamazepine. There is a lack of robust, high-quality evidence from randomised controlled trials. Abstract: Objective: To determine the best available evidence on the efficacy and tolerability of antiepileptic drugs (AEDs) used to treat poststroke seizures and epilepsy. Methods: MEDLINE, Embase, CENTRAL, ClinicalTrials.gov and Opengrey.eu were searched for RCTs of AEDs used to treat post-stroke epilepsy. The following outcomes were considered: seizure freedom; occurrence of adverse effects (AEs); withdrawal for AEs. The methodological quality was assessed according to the Cochrane Handbook for Systematic Reviews of Interventions. Adjusted indirect comparisons were made between each AED using controlled-release carbamazepine (CR-CBZ) as common comparator. Results: Only 2 RCTs were included, one comparing levetiracetam (LEV) with CR-CBZ and the other comparing lamotrigine (LTG) with CR-CBZ. No significant difference was found in seizure freedom between either LEV or LTG and CR-CBZ. Occurrence of AEs were lower for LEV and LTG than for CR-CBZ. Indirect comparisons showed no difference between LEV and LTG for seizure freedom (OR 0.86; 95%CI: 0.15–4.89). Occurrence of AEs was higher for LEV than for LTG (OR 6.87; 95%CI: 1.15–41.1). For withdrawal rates due to AEs, we found a large width and asymmetrical distribution of confidence intervals around the obtained OR of 10.8 (95% CI: 0.78–149.71). Conclusions: Direct and indirect comparisons did not find a difference in seizure freedom between the various AEDs, probably because of the small number of patients included. LEV and LTG appears better tolerated than CR-CBZ and LEV seems associated with more AEs than LTG. Further studies are required to provide robust evidence on efficacy and tolerability of AEDs for treating poststroke epilepsy.